Productivity of fertirrigated sugarcane in subsurface drip irrigation system (International Journal of Irrigation and Water Management, 2021)
The productivity and fresh phytomass index of sugarcane cultivated at different water replacement levels using a subsurface drip system, with or without N, were analyzed. Sugarcane plants underwent five water replacement levels (100, 75, 50, 25 and 0%), with or without N application (100 kg ha-1 ) in urea. At harvest-time, stalk productivity, water-use efficiency, gross sugar yield, gross alcohol yield, fresh phytomass of tip, dry leaf phytomass, total fresh phytomass and the ratio between the fresh phytomass of tip and stalk productivity were evaluated. A 100% water replacement increased stalk productivity by 40% compared with drought-stricken area management (water replacement 0%) and high efficiency in the exploitation of photoassimilated in stalk production. N-urea application increased by 14% the gross sugar and alcohol yield. Water deficit (water replacement 0%) caused severe decrease (26%) in total phytomass of the sugarcane plant´s aerial section.